2020
DOI: 10.3390/ani10060950
|View full text |Cite
|
Sign up to set email alerts
|

Aversion to Desflurane and Isoflurane in Sprague-Dawley Rats (Rattus norvegicus)

Abstract: Carbon dioxide and isoflurane are widely used for killing rats, yet may not truly achieve “euthanasia”, because they elicit aversion. The inhalant anesthetic desflurane is faster acting than isoflurane, representing a potential refinement. Using an aversion-avoidance paradigm, 24 rats were exposed to isoflurane or desflurane (n = 12 per group) at initial exposure. Fourteen rats were then re-exposed to isoflurane or desflurane (n = 7 per group), after a 7 days washout period. Initial exposure: time to recumbenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…This suggests that the anesthetic stress and physiological response triggered by isoflurane is more marked than that induced by other inhalant, injectable, and physical methods of euthanasia. The present results are in agreement with what other authors have stated regarding isoflurane as a refinement method for CO 2 [ 52 , 62 ] and affirm that precautions should be taken when deciding to use isoflurane as a sole method for the humane killing of research animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that the anesthetic stress and physiological response triggered by isoflurane is more marked than that induced by other inhalant, injectable, and physical methods of euthanasia. The present results are in agreement with what other authors have stated regarding isoflurane as a refinement method for CO 2 [ 52 , 62 ] and affirm that precautions should be taken when deciding to use isoflurane as a sole method for the humane killing of research animals.…”
Section: Discussionsupporting
confidence: 93%
“…Isoflurane administered in G 4 rats is a volatile anesthetic that causes depression in the cardiorespiratory centers, leading to hypoxemia and death [ 26 , 60 ]. Although isoflurane has been considered as a method of CO 2 euthanasia refinement [ 14 , 15 ], in comparison with CO 2 and other volatile anesthetics, isoflurane has mild pungency [ 61 ], causing more aversion responses in laboratory rodents that is possibly due to airway irritation [ 52 , 62 ], air hunger, and dyspnea [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data provide additional evidence that CO 2 euthanasia can be further re ned by adding previous anesthesia. Iso urane induced a fast LOC and in contrast to others 21,23,56 we did not observe adverse reactions. Therefore, a combination of CO 2 with anesthetic gases like iso urane might be suitable to induce a more humane euthanasia by compensating the adverse effects of CO 2 and ensuring unpleasant events like gasping to occur de nitively after LOC.…”
Section: Discussioncontrasting
confidence: 89%
“…Re nement methods for CO 2 exposure have also been explored. Recently, it has been recommended to anesthetize rodents with iso urane before CO 2 exposure; however iso urane could also be aversive [21][22][23] and cause excitement 24 . Additionally, recommendations on the use of CO 2 for euthanasia have recently changed from a low (< 30%) to a high (30-70%) gas displacement rate, without providing a clear rationale for this change 4,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [ 13 , 25 ] contend that this aversion to isoflurane is transient, and is not sustained in the days after exposure, thus eliminating the idea that use of isoflurane during procedures requiring anesthesia has an impact on the use of isoflurane during euthanasia. However, a recent study [ 29 ] found this learned aversion to isoflurane is maintained for up to 7 days after initial exposure to isoflurane. Our study builds on this data.…”
Section: Discussionmentioning
confidence: 99%